2002
DOI: 10.17221/3535-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Effect of defatted soybean flour on the flavour of extruded mixtures with wheat flour

Abstract: Mixtures of wheat semolina, 5% glucose and 0-30% defatted soybean flour were used for the preparation of extruded samples using a pilot plant single screw extruder, maximum temperature being 140°C. The browning reactions were only moderate, the intensities of the trichromatic a* coordinate increased, and some changes were observed in chroma and the odour difference ∆E*. The sensory acceptability improved by increasing the content of soybean flour, the odour intensity increased, and some changes were observed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…In the present study, among the metabolites, aldehydes and furans such as benzeneacetaldehyde, 2-furan-carboxaldehyde, 2-furancarboxaldehyde 5-methyl-, phenyl acetaldehyde, and 2-furanmethanol were found in salt-stressed calli. Some of these metabolites were previously observed in soybean due to lipid oxidation, degradation, and sugar dehydration (Pokorny et al 2000;Lee and Ahn 2009). The present results showed that, under different salt treatments, soybean callus synthesized aldehydes and alcohol.…”
Section: Discussionsupporting
confidence: 70%
“…In the present study, among the metabolites, aldehydes and furans such as benzeneacetaldehyde, 2-furan-carboxaldehyde, 2-furancarboxaldehyde 5-methyl-, phenyl acetaldehyde, and 2-furanmethanol were found in salt-stressed calli. Some of these metabolites were previously observed in soybean due to lipid oxidation, degradation, and sugar dehydration (Pokorny et al 2000;Lee and Ahn 2009). The present results showed that, under different salt treatments, soybean callus synthesized aldehydes and alcohol.…”
Section: Discussionsupporting
confidence: 70%